A construção do saber pedagógico do professor bacharel : percepções de professores do IFMT/Rondonópolis - Costa, Sílvia Maria de Moura Bonjour (2014)
This work is the result of a Research Master Program of Graduate Studies in Education at the Institute of Human and Social Sciences, Federal University of Mato Grosso , Campus Rondonópolis and aimed to: understand the process of construction of pedagogical knowledge of bachelor for the practice of teaching teacher; analyze what the teacher assigns meaning to the teaching profession ; understand the perception of the bachelor teacher and their practice in the construction of pedagogical knowledge process and investigate how the bachelor teacher appropriates the knowledge of teaching . The question that guided the research was : how the bachelor teacher builds pedagogical knowledge for the teaching profession ? The methodology adopted in the research process was interpretive and qualitative research had as instruments of data collection : memorials and semi-structured interviews with 05 graduates teachers . As theoretical interlocutors who would support dialogue about teacher learning and teaching, as well as to build a theoretical position in the field of Pedagogical Knowledge , highlight the following authors : Carvalho (2005 ) , Libâneo (1994 , 2011) , Pimenta ( 2000) , Franco (2008 ) , Tardif (2010 ) , Freire (2011 ) , Mizukami (2002 ) , Cunha (2006 ) , Gauthier (2006 ) , Imbernon (2006 ) , Rios (2001 ) and Veiga (2009 ) . The survey results revealed that the practices of the teachers are graduates grounded in their beliefs and these are being built gradually from early life experiences and over time these beliefs will solidify and giving direction to their actions , which helps the construction of the knowledge necessary for the practice of teaching with practice. Also revealed that being a teacher in technology education involves, for the teachers , the constant search for updates in order to keep up with the dynamic and complex technological environment. However , it was evident in the reports, a feeling of isolation in the search for this update , it is necessary that the institution provides a continuing education program for teachers who work in professional education technological level, aims at building a collective pedagogical do.